Export destination and the skill premium: Evidence from Chinese manufacturing industries - Feicheng Wang; Chris Milner; Juliane Scheffel (Canadian Journal of Economics/Revue canadienne d'économique, 2022)
This paper examines the relationship between average income of export destinations and the skill premium using data of Chinese manufacturing industries from 1995 to 2008. To do so, we construct weighted average GDP per capita across destinations employing within-industry export share to each destination as weights, and then link it with industry-level wages and the skill premium. We find that industries that export more to high-income destinations tend to pay a higher skill premium, suggesting that, on average, skilled workers benefit more from high-income exports than unskilled workers. Our IV estimates confirm a causal relationship, and the results are robust to various specifications. Further results based on firm-level data show consistent evidence. Our paper highlights the role of high-income destination exports in shaping the uneven distributional effects of globalization for different types of workers.
Keywords: 330